Dietary Fibers and Human Health - Megan A. McCrory (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Dietary fiber has long been recognized for its role in digestive function. However, currently there is scientific debate about definitions (descriptive and analytical), optimal intake, and essentiality in the human diet. Dietary fiber is a key substrate for bacterial metabolism in the colon, which makes research on dietary fiber an important issue that complements current interest in the gut microbiota. Dietary fiber is also important for prevention and management of cardiovascular disease, diabetes, obesity, and other chronic diseases. This Special Issue will highlight recent research on dietary fiber content in foods and function in human health, ranging from digestive function to chronic disease prevention and management.